Estimating the Impact of COVID-19 Pandemic Related Lockdown on Utilization of Maternal and Perinatal Health Services in an Urban Neighborhood in Delhi, India - Sinha, Bireshwar; Dudeja, Nonita; Mazumder, Sarmila; Kumar, Tivendra; Adhikary, Priyanka; Roy, Nivedita; Rongsen Chandola, Temsunaro; Mehta, Rajesh; Raina, Neena; Bhandari, Nita (Frontiers in Global Women's Health, 2022)
Objective To estimate utilization of maternal, perinatal healthcare services after the lockdown was implemented in response to the COVID-19 pandemic compared to the period before. Methods This study conducted in Dakshinpuri, an urban neighborhood in Delhi, reports data over a 13-month period which includes the period “before lockdown” i.e., October 1, 2019 to March 21, 2020 and “after lockdown” i.e., March 22 to November 5, 2020. The period “after lockdown” included the lockdown phase (March 22 to May 31, 2020) and unlock phase (June 1 to November 5, 2020). Mothers delivered during this period in the study area were interviewed using semi-structured questionnaires. In-depth interviews (IDIs) were conducted in a subsample to understand the experiences, challenges, and factors for underutilization of healthcare services. Findings The survey covered a total population of 21,025 in 4,762 households; 199 eligible mothers (mean age 27.4 years) were interviewed. In women who delivered after lockdown against before lockdown, adjusted odds of having >2 antenatal care visits in the third trimester was 80% lower (aOR 0.2, 95% CI 0.1–0.5); proportion of institutional deliveries was lower (93 vs. 97%); exclusive breastfeeding during first 6 months of birth (64.5 vs. 75.7%) and health worker home visitation within 6 weeks of birth (median, 1 vs. 3 visits) were substantially lower. Fear of contracting COVID-19, poor quality of services, lack of transportation and financial constraints were key issues faced by mothers in accessing health care. More than three-fourth (81%) of the mothers reported feeling down, depressed or hopeless after lockdown. The major factors for stress during lockdown was financial reasons (70%), followed by health-related concerns. Conclusion COVID-19 pandemic-related lockdown substantially affected maternal and perinatal healthcare utilization and service delivery.